Cost and Benefit Kebijakan Bea Perolehan Hak Atas Tanah Dan Bangunan di Provinsi DKI Jakarta - Sonya Whisty Yogyandaru; Ima Mayasari (Profita : Komunikasi Ilmiah Akuntansi dan Perpajakan, 2021)
The policy of the imposition of 0% (zero percent) of the Land and Building Tax in DKI Jakarta based on Governor Regulation Number 126 Year 2017 has been implemented for a period of 4 (four) years. In practice the implementation found many advantages and disadvantages of applying the policy. The purpose of this study is to describe the strengths and weaknesses of the implementation of exemption BPHTB policy. This study uses descriptive qualitative methods that provide an explanation and understanding of the phenomena that occur with tax incentives. The results of the study show the advantages of this policy are to ease the tax burden on the middle to lower class of society to be able to have a house in DKI Jakarta and to encourage the acceleration of land certification. While the weakness of applying the policy is that many taxpayers do tax avoidance by utilizing loopholes in the Governor's Regulation to be able to enjoy this taxation facility